English for Islamic Philosophy: A Development of Digital Dictionary of English Loanword - Mustopa, Mustopa; Mustafa, Mutakhirani (Buletin Al-Turas, 2024)
PurposeThe aim of this research was to investigate the suitability of loanwords to the needs of students majoring in Islamic philosophy, analyze the design interface of the English loanword dictionary application, and understand how they access and use the dictionary. MethodThis study made uses of Research & Development design, a research method used to produce a work or product. The first stage is the preliminary research stage, followed by the product development stage, then the model validation stage, the trial effectiveness stage, and finally, the dissemination or publication and product socialization stage. The research engaged the students and the lecturers as the key informant taken randomly from the Islamic philosophy study program. The data were analyzed qualitatively using the concept of friendly android bilingual dictionary.Results/findingsThe research findings indicated that an English loanword dictionary with comprehensive features was highly beneficial for Islamic philosophy students. This dictionary helped students to understand the terms, and use them in their contexts of Islamic philosophy. The application's user-friendly features enhanced accessibility, with a clear home screen and intuitive navigation.ConclusionThe study concluded that the loanword app played significant role in helping students understanding Islamic philosophy terminology. Future research could explore the app's impact on students' academic performance, language proficiency, and critical thinking skills.